RELATIONSHIP BETWEEN SOCIALIZATION AND ATTITUDE TOWARDS GERIATRIC CARE AMONG CLINICAL OFFICERS IN NAIROBI CITY COUNTY HEALTH CENTERS, KENYA - Dorothy Wanjiku Mwaura; Ruthie C. Rono; Josephine N. Musau, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The rapid growth of the elderly population in Africa poses significant healthcare challenges due to scarcity of geriatric care workers The scarcity can be partially attributed to the attitude towards elderly care. This current study was conducted in Nairobi, Kenya to investigate the attitude of clinical officers towards geriatric care and explore the relationship between their attitude and their socialization. Using a cross-sectional research design, the study involved 302 clinical officers working in 99 health centres across Nairobi City County. Data was collected using a structured questionnaire and subjected to descriptive statistical analysis and the chi-square test. The findings indicated that 58% of the respondents held a positive attitude towards elderly patients, while 42% displayed a negative attitude. Notably, socialization was found to be significantly associated with attitude towards geriatric care c2(1) =10.204, p<.05. The study's results underscore the crucial role of socialization in shaping and influencing the attitude of clinical officers towards geriatric care in Nairobi's healthcare facilities. By leveraging on clinical officers as socialisation agents, healthcare systems can strive to provide better care for the expanding pool of geriatric caregivers in the country.